Developing Self-Regulation, Delinquency Trajectories, and Juvenile Justice Outcomes in Young Women, Pittsburgh, Pennsylvania, 1999-2016 - Hipwell, Alison ([Verlag nicht ermittelbar], 2019)
There is much variability in the adult outcomes of youth who have been involved in the Juvenile Justice System (JJS). It is increasingly recognized that disparate outcomes may reflect the extent to which JJS involvement intersects with developmental patterns of delinquency and is attuned to normative adolescent development, such as maturing self-regulation. However, little is known about the ways in which JJS services influence maturing self-regulation, and how change in these processes will impact delinquency trajectories extending through early adulthood. Even less is known about the impact of JJS on developmental trajectories of delinquency and self-regulation in adolescent girls, despite the rapid increase of girls' involvement in the JJS in recent years. The goal of the current study was to advance knowledge to support effective JJS programs and policies by examining the interface between adolescent self-regulation development, delinquency, and JJS involvement. This project built on the Pittsburgh Girls Study (PGS): a large, longitudinal, racially diverse, urban community sample of females that had been followed annually for 13 years since childhood. New data were collected with support from grant 2013-JF-FX-0058 from a subset of PGS participants at ages 19 and 20 years to capture patterns of delinquency persistence and desistance and to assess outcomes in young adulthood. At the end of the funding period, 88% of the original sample of participants had been interviewed through age 20. In addition, official juvenile justice criminal records were gathered for all 2,450 PGS participants. Analyses were conducted to examine: 1) the impact of JJS involvement on developmental trajectories of delinquency and young adult adjustment; 2) the impact of JJS involvement on self-regulation maturation; 3) the relationship between self-regulation development and change in delinquency and young adult adjustment; and 4) mechanisms during adolescence that explain the link between JJS involvement and delinquency. Results showed JJS involvement predicted concurrent and subsequent changes in self-control during adolescence as well as increased risk for subsequent delinquent behavior, poor educational attainment, employment status, and less satisfaction with life in young adulthood. Moreover, self-control in adolescence partially mediated several of the observed prospective associations between JJS involvement and young adult outcomes. These findings add to a research base that can help policymakers better understand how JJS interventions impact normative developmental processes in ways that influence the course of delinquency. Such information is a critical step in improving outcomes of adolescent girls involved in the JJS through the improvement of interventions promoting self-regulation maturation, accountability, resilience and desistance.